The Current and Future State of China's Pharmaceutical Industry - Goh, Ming Tze (2010)
The report is part of the individual study made to complement the Group Management Project with an examination of China’s current and future role in the global pharmaceutical industry. The report represents the individual component of the group project by providing an understanding of the rising competition from pharmaceutical companies like China that is becoming the main source of pharmaceutical products in the European Union (‘EU’) region as outlined in the exploration of future scenarios for the region in the year 2030. Through the analysis of the current state of China’s pharmaceuticals industry, future businesses within the generics market in the EU can determine the best strategic decisions to make with consideration of the presence of the Chinese companies operating within the EU environment in the coming years.